The impact of shift work on paramedics and their practice: Protocol for a simulated paramedic shift work study - Laura M. Hirello; Sean P. A. Drummond; Kelly-Ann Bowles; Alexander P. Wolkow (PLoS ONE, 2025)
Paramedics make up an integral part of modern healthcare systems, however, there remains a paucity of research on the occupational demands of their role. The majority of paramedics in Australia work on a rotating shift schedule. Despite the documented impact of shift work on sleep loss, and resultant performance and physiological impairments, few studies have examined the implications of shift work in paramedic populations. This study explores the impact of shift work, and the resultant circadian rhythm disruption, on paramedic decision making, work performance and underlying physiology. The study aims to recruit 22 Australian paramedics with an entry to practice scope. In pairs, participants complete a two 12-hour day shift, two 12-hour night shift simulated work rotation. All sleep opportunities during the rotation occur in the Monash Sleep and Circadian Medicine Laboratory and are monitored with polysomnography. Simulated paramedic shifts take place in the Monash Paramedic Simulation Centre, where participants engage in high-fidelity immersive paramedic scenarios throughout the shift. Paramedic scenarios are recorded for asynchronous evaluation by subject matter experts. In addition to paramedic scenarios, participants complete two cognitive and decision-making batteries during each shift. Biological markers are also collected throughout the rotation to assess changes in paramedics’ stress responses (i.e., alpha-amylase, cortisol, heart rate variability, cytokines), as well as circadian phase (i.e., 6-sulfatoxymelatonin). The novel simulated work environment study design contributes significantly to the paramedic body of literature through advancing our understanding of the impacts of shift work on paramedics. This study provides valuable insights into the nature of paramedic work and generates future research directions that will allow for further examination and understanding of the occupational demands of the paramedic profession.